Exploring the relationship between vitamin D levels and body mass index in women with polycystic ovary syndrome - Ashraf Moini; Mohadese Dashtkoohi; Fedyeh Haghollahi; Amene Abiri; Nooshan Tajik (BMC Nutrition)
Abstract Background Polycystic Ovary Syndrome (PCOS) is frequently linked to obesity and insulin resistance, both of which can affect vitamin D metabolism. Although interest in the role of vitamin D in PCOS has increased, the relationship between body mass index (BMI) and vitamin D levels in these individuals remains uncertain. This study explores the connection between serum vitamin D levels and BMI in women with PCOS. Methods This study is a secondary analysis of a cross-sectional investigation carried out from March 2021 to December 2023, including 1004 women with PCOS diagnosed based on the Rotterdam criteria. Statistical methods involved using Spearman’s correlation coefficient to evaluate the association between BMI and vitamin D concentrations, with comparisons across BMI groups performed using the Kruskal-Wallis test. Results Our study found no significant overall correlation between BMI and vitamin D levels (Rho = 0.035, p = 0.261). The median vitamin D levels were 25 ng/mL (IQR 19–34) for normal BMI, 28 ng/mL (IQR 20–35) for overweight, and 24 ng/mL (IQR 19–35) for obese, with no significant differences across these groups (p = 0.109). However, elevated BMI was consistently associated with lower vitamin D levels in individuals with elevated metabolic parameters such as fasting blood sugar, low-density lipoprotein, and triglycerides. Conclusion These findings indicate that higher BMI is linked to lower vitamin D levels in individuals with elevated metabolic risk factors. However, the weak correlations suggest that BMI may not directly influence vitamin D levels.